Prophylactic and therapeutic antileukemic effects induced by the AAC-11-derived Peptide RT53. (1st January 2020) - Habault, Justine; Kaci, Anna; Pasquereau-Kotula, Ewa; Fraser, Claire; Chomienne, Christine; Dombret, Hervé; Braun, Thorsten; Pla, Marika; Poyet, Jean-Luc
ABSTRACT: Despite considerable progress, the treatment of acute leukemia continues to be a challenge for a significant majority of patients. Using a well-characterized preclinical mouse model of acute promyelocytic leukemia (APL), we evaluated here the antileukemic efficacy of RT53, an anticancer peptide with potential immunological properties. Our results indicate that RT53 possesses a direct antileukemic effect, even at a late stage. We also demonstrate that a single injection of a vaccine consisting of leukemic blasts exposed to RT53, which induces the hallmarks of immunogenic cell death, was highly effective in preventing leukemia development in both prophylactic and therapeutic settings. The vaccine comprising RT53-treated APL cells generated long-term antileukemic protection and depletion experiments indicated that CD4 + T cells were of crucial importance for vaccine efficacy. Combined, our results provide the rationale for the exploration of RT53-based therapies for the treatment of acute leukemia.